A Study on the Interplay between Creativity and Aggression in Secondary School Student - Naveed, Tayyaba; Chethiyar, Saralah Devi Mariamdaran; Arshad, Muhammad Zulqarnain (International Journal of Rehabilitation and Special Education (IJRSE), 2023)
The purpose of this study is to evaluate, among secondary school students, whether  or whether there is a connection between creative expression and aggressive  behavior. Purposive random selection was used to choose students for the study  from two secondary schools located in Sahiwal city: Government Girls Model Pilot  Secondary School and Lasani public school. The total number of students that  participated in the study was one hundred. The Creative Personality Scale (CPS)  and the Buss-Perry Aggression Questionnaire were applied in this study so that  the researchers could examine the association between creativity and aggression.  The data suggest that there is an inverse relationship between creative output  and aggressive behavior among secondary school pupils. However, there was no  discernible gap found between the sexes in terms of creative output. In addition,  the findings of the study indicate that male students are more likely to engage  in aggressive behavior than their female counterparts. In addition, the findings  indicate that students in government and private schools’ 10th grade, who are aged  16 to 18, are more creative than students in government and private schools’ 9th  grade, who are aged 13 to 15.
Keywords: Creativity; Aggression; Creative Personality Scale; Stimulation